2021
DOI: 10.1096/fj.202002539r
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophage‐mediated therapy of chondrosarcoma by selective delivery of the tumor necrosis factor alpha (TNFα) gene

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…Most research on phages in SEA consists of genetic studies, including genomic characterization of phages and bioengineering applications, such as phage typing and phage display. In terms of bioengineering phages for therapeutic applications, SEA scientists reported the use of phages for targeted gene therapy (Namdee et al, 2018;Przystal et al, 2019;Chongchai et al, 2021) and adaptation of nanomaterial-based phage delivery systems (Adamu Ahmad et al, 2016;Kaikabo et al, 2017). There is also a notable amount of research on in vitro testing of phages, including the testing for the phage's host range, biocontrol assays against pathogens, and phage formulation techniques.…”
Section: Phage Research In Seamentioning
confidence: 99%
See 1 more Smart Citation
“…Most research on phages in SEA consists of genetic studies, including genomic characterization of phages and bioengineering applications, such as phage typing and phage display. In terms of bioengineering phages for therapeutic applications, SEA scientists reported the use of phages for targeted gene therapy (Namdee et al, 2018;Przystal et al, 2019;Chongchai et al, 2021) and adaptation of nanomaterial-based phage delivery systems (Adamu Ahmad et al, 2016;Kaikabo et al, 2017). There is also a notable amount of research on in vitro testing of phages, including the testing for the phage's host range, biocontrol assays against pathogens, and phage formulation techniques.…”
Section: Phage Research In Seamentioning
confidence: 99%
“…DotBio, a start-up biotechnology company in Singapore, utilizes the phage display technique to produce DotBody technology proposed to be used in multi-functional therapies (https://www.dotbio.com/en/ technology, accessed 20 December 2021). Meanwhile, scientists from SEA reported bioengineered phages with applications as vectors for selective delivery of transgenes in mammalian cells via phage surface modification (Namdee et al, 2018;Chongchai et al, 2021) and dual tumor targeting by hybridization of an adeno-associated virus with the phage capsid (Przystal et al, 2019). However, no specific modifications have been done to create phages specifically targeting clinically relevant bacteria.…”
Section: Phase Two: Laboratory-and Clinic-based Phage Therapy Applicationsmentioning
confidence: 99%
“…Notably, recent studies have shown that the functionalization of TNF-bearing gold nanoparticles with NGR- or isoDGR-containing ligands can enable also the “active” targeted delivery of extremely low, but pharmacologically active, doses of nanodrug (e.g., equivalent to 5 pg of biologically active TNF/mouse) to the tumor vasculature in murine models [ 64 , 86 ]. Finally, genetically modified viruses, bacteria, and bacteriophages, engineered to express TNF alone or in combination with other cytokines, have also been developed [ 87 , 88 , 89 , 90 , 91 , 92 , 93 ]. For example, a recent study performed in a murine model of human glioblastoma have shown that an RGD4C-directed hybrid virus of adeno-associated virus and phage (AAVP) can deliver the TNF gene to the tumors, and induce damage of tumor-associated neovessels and cell death [ 94 ].…”
Section: Clinical Studies With Ngr-tnfmentioning
confidence: 99%
“…When chondrosarcoma SW1353 cells were exposed to the phage vector encoding a TNFα transgene, distinct targeted cell killing concomitant with the high expression of TNFα and apoptosis-related genes was witnessed. In vivo, chondrosarcoma implant-carrying mice exhibited inhibition of tumor growth post phage vector administration ( Figure 3 ) [ 108 ]. In another study, phage mediated gene replacement therapy was attempted.…”
Section: Using Phages To Target and Regulate Tumor And Its Microenvironmentmentioning
confidence: 99%